2022
DOI: 10.1200/edbk_349143
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA: An Emerging Tool in Gastrointestinal Cancers

Abstract: Circulating tumor DNA (ctDNA) is tumor-derived fragmented DNA in the bloodstream that has come from primary or metastatic cancer sites. Neoplasm-specific genetic and epigenetic abnormalities are increasingly being identified through liquid biopsy: a novel, minimally invasive technique used to isolate and analyze ctDNA in the peripheral circulation. Liquid biopsy and other emerging ctDNA technologies represent a paradigm shift in cancer diagnostics because they allow for the detection of minimal residual diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 159 publications
0
32
0
Order By: Relevance
“…39 The possibility of using ctDNA as a surrogate for treatment response and survival is an attractive concept; this surrogate will arguably reduce study duration and expedite the development of new therapies. 40 Some studies have reported that monitoring ctDNA can reflect treatment response, monitor disease progression, and facilitate prediction of prognosis in some solid cancers. 39,[41][42][43] Recently, some research reported that ctDNA had prognostic value in lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The possibility of using ctDNA as a surrogate for treatment response and survival is an attractive concept; this surrogate will arguably reduce study duration and expedite the development of new therapies. 40 Some studies have reported that monitoring ctDNA can reflect treatment response, monitor disease progression, and facilitate prediction of prognosis in some solid cancers. 39,[41][42][43] Recently, some research reported that ctDNA had prognostic value in lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
“… 33 ctDNA analysis has increased sensitivity and specificity compared with the analysis of other circulating biomarkers and SUVmax. 28 , 50 , 51 Moreover, ctDNA provides a dynamic real-time profiling and identifies these novel mutations in a timely manner on serial monitoring independently, making it the ideal tool for monitoring minimal residual disease (MRD) in ENKTL, 40 , 52 and could correct tumor heterogeneity and biopsy site bias. Recently, a new model of a 7-SNP-based classifier based on the status of seven single-nucleotide polymorphisms (SNPs) was constructed for ENKTL, which initiated the use of molecular mutations to construct prognostic model for ENKTL.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of MRD by measuring circulating tumor DNA (ctDNA) levels may facilitate individualized adjuvant therapy and improve survival outcomes in patients with GC. However, data on the clinical use of ctDNA in GC are limited, requiring further studies for its clinical application [6]. Given the dissatisfaction with the established biomarkers, further research to develop accurate and novel biomarkers are necessary.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…1 Several ongoing clinical studies have been designed to expand the scope of ctDNA-informed treatment decisions in gastrointestinal (GI) cancers. 1,2 Although expansion of ctDNA-based treatment decisions is a necessary advancement in cancer care, it is crucial to understand the limitations of this test and thereby the clinical situations in which ctDNA liquid biopsy may not be entirely reliable. A growing body of evidence shows the interaction of tumor type, tumor burden, and site of metastases on the amount of ctDNA detected in the blood.…”
mentioning
confidence: 99%
“… 1 Several ongoing clinical studies have been designed to expand the scope of ctDNA-informed treatment decisions in gastrointestinal (GI) cancers. 1 , 2 …”
mentioning
confidence: 99%